(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
This article presents the results of a study on the treatment of mulberry trees with the modern drug Gumimax Silkworm and the feeding of silkworms with these leaves. The conclusions on the positive effect of this drug on the biological and productivity indicators of silkworm have been raised. In particular, it was found that the mass of the silkworm increased by 3,1-4,5 g in the experimental variants compared to the control, the viability of the worms fed with the test preparation was higher by 10,6 % compared to the control variant, it is known that the number of healthy cocoons is 8-12 % higher than in the control. It was also found that the mass of one cocoon is 0,8-1,5 g heavier than the control in the experimental variants, there were no signs of poisoning, the occurrence of diseases and a lag in the development of the silkworm. It should be noted that as a result of the treatment of mulberry trees with the investigated "Gumimax" - a double-acting drug, the amount of substances necessary for the growth and development of silkworms in the composition of the leaves increases, and the quality of the leaves increases due to the acceleration of the photosynthesis process, which in turn indicates food satiety and acceleration of the metabolic process in the body of the silkworm, i.e., about improving the digestibility, digestibility of feed